2019
DOI: 10.4103/ijo.ijo_500_18
|View full text |Cite
|
Sign up to set email alerts
|

Types of organisms and in-vitro susceptibility of bacterial isolates from patients with microbial keratitis: A trend analysis of 8 years

Abstract: Purpose:To report the distribution and trends of types of organisms and antibiotic susceptibility of the bacterial isolates obtained from patients with microbial keratitis.Methods:Microbiology records of culture-positive microbial keratitis that underwent a diagnostic corneal scraping and cultures were reviewed. Fungal, bacterial, and parasitic culture results and antibiotic susceptibility profile of bacteria were analyzed and comparisons were made between two halves of the study period (2007–2010 vs. 2011–201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
30
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 30 publications
6
30
2
1
Order By: Relevance
“…have been the most commonly isolated organisms. 24 In our study, both showed good sensitivity to vancomycin (>90%) and variable sensitivity to various fluoroquinolones. A recent update from South India showed similar sensitivity toward vancomycin; however, they had good sensitivity toward fluoroquinolones as well, 11 which was not seen in our patients.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…have been the most commonly isolated organisms. 24 In our study, both showed good sensitivity to vancomycin (>90%) and variable sensitivity to various fluoroquinolones. A recent update from South India showed similar sensitivity toward vancomycin; however, they had good sensitivity toward fluoroquinolones as well, 11 which was not seen in our patients.…”
Section: Discussionsupporting
confidence: 50%
“…It was most sensitive to imipenem. Other studies have showed better sensitivity patterns, 11 but at the same time, one should not miss the worrying trends of multidrug-resistant Pseudomonas spp. from around the world, 25 26 a reflection of which we are also beginning to see in our clinics.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…They found that the antibiotic resistance rates in ocular isolates have been stable [24] however, a recent report from Das et al found a significant decrease in susceptibility in Pseudomonas spp. isolated from keratitis patients to a fourth generation fluoroquinolone, moxifloxacin [25], suggesting a rise in antibiotic resistance in Pseudomonas spp. Various studies have investigated the virulence factors in clinical isolates from diseases such as cystic fibrosis, respiratory infections, septicemia, and keratitis [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…We read with great interest the article titled “Types of organisms and in-vitro susceptibility of bacterial isolates from patients with microbial keratitis: A trend analysis of 8 years” by Das et al . [1] As a tertiary eye care provider and one of the biggest cornea departments in north India, we congratulate the authors for their brilliant work, would like to use this opportunity to reflect upon, and compare the microbial profile and antibiotic sensitivity seen in our practice. We agree with the authors that local epidemiological studies are required to provide evidence-based management of microbial keratitis,[1] and hence, wanted to add our data from north India to their study, to give a pan India perspective to our readers.…”
mentioning
confidence: 99%